A Rare Case of Lung Hypoplasia in a 1-Year-Old Girl (The Review of Diabetic Studies, 2024)
Pulmonary hypoplasia is a rare form of congenital disorder that leads to lung underdevelopment. It is more common in children and infrequently noticed in adulthood. While congenital lung abnormalities are frequently discovered in the early years of life, these conditions are also often detected incidentally following routine radiographic imaging and investigations. We report the case of a 1-year-old girl who presented to the emergency department with a three-day history of cough, shortness of breath, fever, and respiratory distress. Investigations revealed right lung hypoplasia, left lung hyperinflation, and an invisible pulmonary artery and vein. A diagnosis of right lung hypoplasia as an incidental finding with associated anomalies was made. She was admitted to the pediatric ward and received supportive care and empirical antibiotics. She was then discharged in a good condition with supportive management for follow-up. This case report aims to describe a rare condition occurring in children with various clinical pictures and presentations to aid the future early detection to achieve better diagnostic outcomes.